PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA E-COMMERCE GROCERY ONLINE SEGARI - Mutiara Kanza (2022)
The type of research used by researchers is quantitative research which aims to determine the effect of service quality on customer loyalty, the effect of product quality on customer loyalty, the effect of customer satisfaction on customer loyalty, the effect of service quality indirectly on customer loyalty through customer satisfaction, and the effect of quality. product indirectly to customer loyalty through customer satisfaction. This study uses primary data sources. The population in this study are Segari customers who live in the DKI Jakarta area. The sample used amounted to 100 respondents. The sampling technique in this study used non-probability sampling with purposive sampling method. Data collection was carried out in this study using online questionnaires using Google Form facilities such as Whatshapp, Line and Instagram. This study used the SEM method with the SmartPLS software test tool. The research obtained the results: the service quality variable had a positive and significant effect on customer loyalty with an original sample value of 0.320. The product quality variable has no significant effect on customer loyalty with an original sample value of 0.201. Customer satisfaction has a positive and significant effect on customer loyalty with an original sample value of 0.431. Service quality indirectly has a positive and significant effect on customer loyalty through customer satisfaction with an original sample value of 0.245. As well as product quality indirectly has a positive and significant effect on customer loyalty through customer satisfaction with an original sample value of 0.152.